When Should Naloxone Be Administered to the Undifferentiated Unresponsive Person? (International Journal of First Aid Education)
Despite deaths from opioid overdose having increased significantly in recent years, the ARC SAC advise that administering Naloxone, which can reverse the effects of an overdose, should not be prioritized in undifferentiated patients experiencing cardiac arrest over currently accepted resuscitation techniques, as coronary artery disease is nearly ten times more likely than opioid overdose to be the cause.